A novel transmissibility matrix method for identifying partially coherent noise sources on vehicles. (August 2020) - Wang, Chenguang; Jiang, Weikang
Abstract: For vehicle interior sound field, it is difficult to identify locations of main sources due to the coupling of transmission paths. The traditional operational transfer path analysis (OTPA) is unable to be used to get the contribution of partially coherent sources. A transmissibility matrix identification (TMI) method is proposed to deal with partially coherent source identification problem. Partially coherent radiation sources are located on the body panel structure and microphones are set to record sound signals. The transmissibility of sound from microphone near the partially coherent radiation source to the microphone away from the source should be smaller than the converse transmissibility. Locations of main sound sources are determined by finding the transmissibility matrix with the smallest Frobenius norm. Comparing with partial singular value decomposition (PSVD) method which is based on independent source hypothesis, main sources locations obtained by TMI method are more stable. The method was verified by experiments in the semi-anechoic chamber and successfully applied to the identification of internal noise sources in vehicles. The relationship between various sources was clear by the calculation of the partial contribution of each partially coherent source and the aliasing rate of the system.